'Le concerto pour Éclair et Nagra': a sonic snapshot of Paris in Le Joli mai (1963). Issue 3 (1st October 2020) - Anderson, Laura
ABSTRACT: Chris Marker and Pierre Lhomme's Le Joli mai documents Paris in May 1962 – the first month of peace after the Evian agreements brought a conclusion to the Algerian War. It is a film that is often discussed in relation to its importance as a sociological text and for its artistic value. Yet, its importance as a milestone in the history of French film sound design remains to be explored. This article will consider how emerging technologies shaped the production process of Le Joli mai, where sonic considerations often led decision making about the images in a reversal of the conventional image-sound hierarchy. While the film employs a score by Michel Legrand and the voice of Yves Montand, smooth integration of the soundscape is destabilised due to the desire to capture real-world sounds and atmosphere. The article situates Le Joli mai at the nexus of sonic tradition and innovation, considering the film in relation to documentary sound, song in French cinema and the innovations of contemporary New Wave film. It argues that Le Joli mai presents a model of French film sound design that reflected social disruption sonically and paralleled ongoing polemics of early 1960s France.